Implementasi Jaminan Halal pada Program Makan Bergizi Gratis (MBG) di Kecamatan Medan Timur - Rayhan, Muhammad; Zulham (AL-SULTHANIYAH, 2025)
This study examines the implementation of the Free Nutritious Meal (MBG) Program in Medan Timur District, focusing on compliance with the Halal Product Assurance (JPH) as mandated by Law Number 33 of 2014. Employing a qualitative approach through interviews, observations, and document analysis, the research reveals a gap between regulatory provisions and on-the-ground practices. While the MBG program aims to improve human resource quality, reduce malnutrition and stunting, and stimulate regional economic growth, its implementation still faces challenges, including the absence of halal labels and expiration dates on some products, incomplete halal certification of food suppliers, limited infrastructure, shortage of halal auditors, weak inter-agency coordination, and budget constraints. These conditions indicate that the protection of Muslim consumers’ rights to halal and thayyib food has not been fully ensured. The study recommends strengthening technical regulations, accelerating halal certification, enhancing monitoring systems, and fostering multi-stakeholder collaboration to ensure the program’s success in line with legal mandates and Islamic principles.